A Literature Study on the Marketing Environment - MEHRA, AASHISH; JAIN, VIBHOR (The journal of contemporary issues in business and government, 2021)
In recent years, the globalization of modern organization projects too is growing and may theoretically lead to a wider range of macroeconomic participants seeking overseas markets. Empirical analyses have shown that the development and development through cross- border entrepreneurship can be viewed in the context of the dramatic developments that have taken place over the last decades, which have contributed to a decrease in transaction fees for multinational organizations. The main purpose of this study is to explain the significance of the interaction between the different elements of the marketing environment to gain a strategic edge in the industry. The political, social and technical environment has a great deal of impact on entrepreneurial progress in global markets. The focus of this research is to consider the obstacles which entrepreneurial companies face in attempting to introduce their brands to global marketing. This research followed a secondary method towards collecting data through examining archival literature of inquiry. This study concludes whereby cross-border organization practices are important avenues from which aspiring entrepreneurs can build value, drive development as well as access new information and innovations by their exposure towards international markets.